2022
DOI: 10.3389/fcvm.2022.897733
|View full text |Cite
|
Sign up to set email alerts
|

Increased BMI and Blood Lipids Are Associated With a Hypercoagulable State in the Moli-sani Cohort

Abstract: The coagulation system can be assessed by the thrombin generation (TG) assay, and increased TG peak height, endogenous thrombin potential (ETP), and velocity index are associated with an increased risk of thrombosis. Obesity had been reported to increase TG and is associated with dyslipidemia, which also predisposes to atherosclerotic cardiovascular disease (CVD). However, the effect of the blood lipid profile on TG has not been studied extensively. To gain more insight into the associations of TG, body mass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…However, the specificity and AUC of combined parameters, namely peak time, peak height, and blood flow rate, were significantly higher than those of single parameters. These results underscore the diagnostic efficacy of combining these parameters derived from MSCT perfusion imaging in assessing the risk of peripancreatic infection in elderly SAP patients [ 30 ].…”
Section: Discussionmentioning
confidence: 88%
“…However, the specificity and AUC of combined parameters, namely peak time, peak height, and blood flow rate, were significantly higher than those of single parameters. These results underscore the diagnostic efficacy of combining these parameters derived from MSCT perfusion imaging in assessing the risk of peripancreatic infection in elderly SAP patients [ 30 ].…”
Section: Discussionmentioning
confidence: 88%
“…Obesity has become a pandemic, increasing risks for arterial, venous, and microvascular thrombosis, including myocardial infarction, ischemic stroke, venous thromboembolism, and thrombotic thrombocytopenic purpura. 93 Seventy percentage of obese people have dyslipidemia, 94 which is independently associated with thrombosis, 95–97 suggesting dyslipidemia could be one of the causal mechanisms driving thrombosis in obesity. Obesity-associated dyslipidemia is characterized by higher plasma apoB-lipoproteins cholesterol and triglyceride, due to increased hepatic and intestinal apoB-lipoprotein production, 98,99 decreased apoB-lipoprotein clearance, and reduced HDL cholesterol.…”
Section: Thrombotic Tendency In Obesity and Dyslipidemiamentioning
confidence: 99%
“…History of asthma since childhood, experiencing shortness of breath to a bluish body, others denied, history of premature birth. The results of the physical examination GCS E3-4M6V5, blood pressure 115/71 mmHg, HR 70x/minute, regular, temperature 36.5, RR 18x/minute, BMI 25.95 (Obesity 1) in many individuals with obesity, changes in the hemostatic and fibrinolytic activity are observed that lead to hypercoagulability 10 , general status within normal limits, neurological status paresis N VII dextra Central, negative dysphagia screening, CT Scan results while in the NBC hospital ER are acute infarction in the left medial temporal lobe and old infarction in the left frontal lobe (median gyrus) while chest X-ray images while in the NBC ER are no abnormalities in heart and lungs.…”
Section: Case Reportmentioning
confidence: 99%